VALUASI SAHAM PERUSAHAAN KASUS PT FS - , Wahyu Edi Winoto; , Prof. Dr. Sukmawati Sukamulja., MM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The thesis discuss about stock valuation of PT FS (âFSâ), a coal mining company using Discounted Cash flow method based on free cash flow to equity (FCFE). PT FS was acquired by Bumi Resources on early 2009. Initially, Bumi proposing to acquire 76.7% of FSâ share for IDR 2.7 trillion based on 100% valuation of IDR 3.2 trillion. The proposed transaction then revised by Bapepam, the corrected value is IDR 2.7 trillion for 100% share. Based on the Bapepam valuation, Bumi decided to change the acquisition structure by acquire only 50% FSâs share. On 2010, FS has completed the reserve calculation using JORC method and the shareholder is planning to sell the remaining shares. The main purpose of this thesis is to evaluate the stock valuation using the most recent data and information to obtain more accurate value of the company. The methodology used in this valuation done by understanding historical record and operational, as well as analysis of financial performance by considering going concern of the company. Cash flow projection prepared for the six years period by considering historical financial performance, managementâs strategy, and external factors such as macro economy condition as well as coal industry. The valuation on this research provides indication of 100% fair value of the company at IDR 6.2 trillions. The result indicating that the companyâs value is much higher compare to the previous valuation. The main factor causing the difference is the number of coal reserve used as a basis calculation in the current valuation.